To the 10th anniversary of the Shared Use Center "Analytical Center of the Federal State Budgetary Educational Institution of Higher Education of the SPKhFU of the Ministry of Health of Russia" - article Editorial (Разработка и регистрация лекарственных средств)
The Center for Shared Use of Scientific Equipment "Analytical Center of the Federal State Budgetary Educational Institution of Higher Education SPKhFU of the Ministry of Health of Russia" (CKU) was established on the basis of the University in 2011 with the aim of carrying out research in the field of creating highly effective and innovative medicines, taking into account modern scientific approaches and carries out scientific, research and educational functions.